A Systematic Literature Review in Shariah Audit - Arini Arini; An Suci Azzahra; Sambas Ade Kesuma; Iskandar Muda (Journal of Social Science, 2023)
This study aims to present in detail the sharia audit research based on a systematic literature review. From 2013–2023, 40 articles were collected from the Scopus database. This research is seen from a theoretical point of view, geographical distribution, research background, and theme. The results show an increase in Islamic audit research in recent years. Compared to other Islamic countries, most of the research was conducted in specific countries, such as Malaysia. In addition, it has been found that previous studies have not known the antecedents and effects of effective Islamic auditing practices in IPIs, The focus of research on certain theories, such as agency theory, limits the way of research.